2014
DOI: 10.1016/j.semcdb.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Epiregulin: Roles in normal physiology and cancer

Abstract: Epiregulin is a 46-amino acid protein that belongs to the Epidermal Growth Factor (EGF) family of peptide hormones. Epiregulin binds to the EGF receptor (EGFR/ErbB1) and ErbB4 (HER4) and can stimulate signaling of ErbB2 (HER2/Neu) and ErbB3 (HER3) through ligand-induced heterodimerization with a cognate receptor. Epiregulin possesses a range of functions in both normal physiologic states as well as in pathologic conditions. Epiregulin contributes to inflammation, wound healing, tissue repair, and oocyte matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
162
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(169 citation statements)
references
References 98 publications
5
162
1
1
Order By: Relevance
“…Overexpressed EREG has been linked to dysregulation of mitogen-activated protein kinase signaling via the EGF pathway as well as the ERBB pathway, and this overexpression in the sensitive cells may reflect an underlying drive toward the mitogen-activated protein kinase/ERBB pathways. 54,55 Conversely, in the arginase-resistant cells, overexpression of the heat shock protein HSPA6 was demonstrated, suggesting that this may be a mechanism by which these cells attain resistance, especially in light of the finding that HSP inhibition is cytotoxic to AML. 56 EREG and EGFR signaling, as well as the heat shock protein family, play key roles in solid tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressed EREG has been linked to dysregulation of mitogen-activated protein kinase signaling via the EGF pathway as well as the ERBB pathway, and this overexpression in the sensitive cells may reflect an underlying drive toward the mitogen-activated protein kinase/ERBB pathways. 54,55 Conversely, in the arginase-resistant cells, overexpression of the heat shock protein HSPA6 was demonstrated, suggesting that this may be a mechanism by which these cells attain resistance, especially in light of the finding that HSP inhibition is cytotoxic to AML. 56 EREG and EGFR signaling, as well as the heat shock protein family, play key roles in solid tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Epiregulin, a 46-amino acid protein that belongs to the EGF family, binds to the EGF receptor and ERBB4 (HER4), and can stimulate signaling of ERBB3 (HER2/neu) and ERBB3 (HER3). Deregulated epiregulin activity was noted in a variety of cancers, including breast, lung, colon, stomach, bladder, head and neck, and liver, and epiregulin normally regulates ovarian follicle formation and oocyte development 27 . In this report, epiregulin was downregulated after BPA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that curcumin exerts wide-range anti-tumor activities [9]. Curcumin is shown to inhibit cancer cell survival and proliferation, to induce cancer cell death and apoptosis, and to suppress cancer-related angiogenesis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, or 1,7-bis(4-hydroxy-3methoxyphenyl)-1,6-heptadien-3,5-dione, is the main bioactive component of turmeri from the rhizome of Curcuma longa [9]. Studies have confirmed that curcumin exerts wide-range anti-tumor activities [9].…”
Section: Introductionmentioning
confidence: 99%